Investigation of ultrasonic pretreatment on the synthesis of Zeolite-T and its CO2 adsorption characteristics - Yeong, Y.F. (Trans Tech Publications Ltd, 2014)
In the present work, ultrasonic pretreatment method was firstly introduced in synthesizing of zeolite-T. The effect of ultrasonic pre-treatment on the synthesis duration was investigated. The structure and morphology of the resulting zeolite-T were characterized using several analytical tools such as X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and Fourier transfer infrared spectroscopy (FTIR). The CO2 adsorption characteristic of the resulting zeolite-T was determined using CO2 physisorption analyzer. Results showed that by introducing ultrasonic pre-treatment, the crystallization time was reduced from 7 days to 3 days, without affecting the structure, morphology and CO2 adsorption capacity of the resulting zeolite-T. Â© (2014) Trans Tech Publications, Switzerland.